Transcriptional regulation of tocopherol biosynthesis in tomato - Quadrana, Leandro Daniel (2013)
Tocopherols, compounds with vitamin E (VTE) activity, are potent lipid-soluble antioxidants synthesized only by photosynthetic organisms. Their biosynthesis requires the condensation of phytyl-diphosphate and homogentisate, derived from the methylerythritol phosphate (MEP) and shikimate pathways (SK), respectively. These metabolic pathways are central in plant chloroplast metabolism and are involved in the biosynthesis of important molecules such as chlorophyll, carotenoids, aromatic amino-acids and prenylquinones. In the last decade, few studies have provided insights into the regulation of VTE biosynthesis and its accumulation. However, the pathway regulatory mechanism/s at mRNA level remains unclear. We have recently identified a collection of tomato genes involved in tocopherol biosynthesis. In this work, by a dedicated qPCR array platform, the transcript levels of 47 genes, including paralogs, were determined in leaves and across fruit development. Expression data were analyzed for correlation with tocopherol profiles by coregulation network and neural clustering approaches. The results showed that tocopherol biosynthesis is controlled both temporally and spatially however total tocopherol content remains constant. These analyses exposed 18 key genes from MEP, SK, phytol recycling and VTE-core pathways highly associated with VTE content in leaves and fruits. Moreover, genomic analyses of promoter regions suggested that the expression of the tocopherol-core pathway genes is trancriptionally coregulated with specific genes of the upstream pathways. Whilst the transcriptional profiles of the precursor pathway genes would suggest an increase in VTE content across fruit development, the data indicate that in the M82 cultivar phytyl diphosphate supply limits tocopherol biosynthesis in later fruit stages. This is in part due to the decreasing transcript levels of geranylgeranyl reductase (GGDR) which restricts the isoprenoid precursor availability. As a proof of concept, by analyzing a collection of Andean landrace tomato genotypes, the role of the pinpointed genes in determining fruit tocopherol content was confirmed. The results uncovered a finely tuned regulation able to shift the precursor pathways controlling substrate influx for VTE biosynthesis and overcoming endogenous competition for intermediates. The whole set of data allowed to propose that 1-deoxy-D-xylulose-5-phosphate synthase and GGDR encoding genes, which determine phytyl-diphosphate availability, together with enzyme encoding genes involved in chlorophyll-derived phytol metabolism appear as the most plausible targets to be engineered aiming to improve tomato fruit nutritional value.